2010
DOI: 10.1212/wnl.0b013e3181c919d6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of enzyme activity and clinical phenotype in POMT1-associated dystroglycanopathies

Abstract: Our results suggest that dermal fibroblasts can be applied to facilitate the diagnostic analysis of dystroglycanopathy patients as well as to study the pathogenic mechanism of POMT mutations. Characterization of the POMT1 substrate protein alpha-dystroglycan and POMT in vitro mannosyltransferase activity shows that the severity of the clinical phenotype of the patients analyzed is inversely correlated with POMT activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
(28 reference statements)
2
23
2
Order By: Relevance
“…On the other hand, measurement of POMT activity using dermal fibroblasts from POMT1-mutated patients showed that clinical phenotype severity is inversely correlated with POMT1 activity. 35 A direct correlation between mannosyltransferase activity and clinical severity, however, does not seem to apply to heart involvement, which in our patients appears possible with very different degrees of neuromuscular severity, and with both complete and partial glycosylation defects (detected in the skeletal muscle).…”
Section: Discussioncontrasting
confidence: 57%
“…On the other hand, measurement of POMT activity using dermal fibroblasts from POMT1-mutated patients showed that clinical phenotype severity is inversely correlated with POMT1 activity. 35 A direct correlation between mannosyltransferase activity and clinical severity, however, does not seem to apply to heart involvement, which in our patients appears possible with very different degrees of neuromuscular severity, and with both complete and partial glycosylation defects (detected in the skeletal muscle).…”
Section: Discussioncontrasting
confidence: 57%
“…With respect to FKTN, a patient homozygous for an early nonsense mutation died at 4.5 months, and patients with compound heterozygosity with the Japanese founder mutation and nonsense, frameshift, or exon-skipping mutations are clinically more severely affected than those homozygous for the founder mutation, indicating that disease severity is dependent on the nature of the gene mutation (9,56,57). While we do not yet know the specific activity of FKTN in the αDG processing pathway, we presume that the degree of αDG dysfunction and the disruption of FKTN protein activity will also be positively correlated to the FKTN gene mutation, as has been shown for POMT1 and POMGnT1 enzyme activity in patient cells (58,59).…”
Section: Discussionmentioning
confidence: 90%
“…1E). The observed phenotypic variations could be caused by differences in POMT activity, given that low enzymatic activity was detected for human and zebrafish POMT2 in the absence of POMT1 (13,21). In addition, compared with the levels of the Pomt2 maternal mRNA during the transition from oocyte to morula, the levels of Pomt1 mRNA were strikingly high ( Fig.…”
Section: Resultsmentioning
confidence: 96%